Awareness of civil society with health on cleanlinity of Ciliwung river: study of public response on online news media in DKI Jakarta - Faiq Hilmi Ciptadi (Berita Kedokteran Masyarakat (BKM), 2019)
BACKGROUND : Urban hygiene and sanitation is a public health risk factor. Ciliwung river in DKI Jakarta was known full of garbage piles, and the reports about efforts made to clean the river in the online news has generated responses. This study aims to describe the voice of civil society on public health.METHODS : Case study method was used in online news media about clean Ciliwung river. With the inclusive criteria of commented newsletters with the keyword "Ciliwung bersih" published between April 1, 2015 and April 30, 2017, 57 news were obtained generated through https://news.google.co.id/. But some news with irrelevant themes and commentary were excluded, so 14 news were used. Content analysis is done and the results are described in a narrative-descriptive writing.RESULTS : The government's revitalization policy of the Ciliwung River, followed by the growth of community movements concerned with river cleanliness, has resulted settlement of the Ciliwung river cleanliness issue. From the analysis of 14 news, 3 key themes were obtained which are availability of environmental health for people, existence of health-oriented government with leadership, and active participation of the community. Responses include, happiness and appreciation for the government and society, voice of hope for the clean river and the call to make further environmental health changes.CONCLUSION : The news of clean river invites public response to care about environmental health problems, which provides lessons the ability to visualize the benefits of cleanliness and health rises community awareness.